2005
DOI: 10.1007/s00403-004-0536-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of galectin-3 in primary and metastatic melanoma: immunohistochemical studies on human lesions and nude mice xenograft tumors

Abstract: Galectins are a large family of proteins which bind galactoside-containing glycans. Their role in cancer seems to be important since members of the family may mediate cell adhesion and modulate cell growth. Galectin-3 (Gal-3) is expressed in the nucleus, in the cytoplasm and on the cell surface, and can also be secreted into the extracellular matrix. A series of experimental and clinical data have been reported which indicate that Gal-3 may play a putative role in carcinogenesis, cancer progression and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
4
19
2
1
Order By: Relevance
“…Sarafian et al [39] suggested that LAMP proteins might serve as ligands for cell adhesion molecules and demonstrated in vitro a positive correlation between enhanced galectin-3 binding to LAMP-expressing cells and an increase in the expression of both LAMP-1 and LAMP-2 proteins. On the other hand, however, it was recently demonstrated that the expression of galectin-3 is strong in primary melanomas and drops significantly in more advanced lesions and in melanoma metastases [40]. The results from our study taken together with observations of [40] contradict the results of in-vitro studies by Sarafian et al [39].…”
Section: Discussioncontrasting
confidence: 78%
“…Sarafian et al [39] suggested that LAMP proteins might serve as ligands for cell adhesion molecules and demonstrated in vitro a positive correlation between enhanced galectin-3 binding to LAMP-expressing cells and an increase in the expression of both LAMP-1 and LAMP-2 proteins. On the other hand, however, it was recently demonstrated that the expression of galectin-3 is strong in primary melanomas and drops significantly in more advanced lesions and in melanoma metastases [40]. The results from our study taken together with observations of [40] contradict the results of in-vitro studies by Sarafian et al [39].…”
Section: Discussioncontrasting
confidence: 78%
“…Here, we have demonstrated the involvement of galectin-3 in murine melanoma growth and metastases. We observed prominent expression of galectin-3 in B16F10 cells, a finding that has also been described in other studies dealing with human and murine melanoma cell lines [29,30]. A similar result has previously indicated that the overexpression of galectin-3 may confer a selective survival advantage and a resistance to apoptosis in human breast carcinoma cell lines by specifically in- Figure 3.…”
Section: Discussionsupporting
confidence: 74%
“…Thick tumors exhibited weak intensity, whereas thin tumors manifested intermediate staining intensity. The same finding was observed in a study using a melanoma cell line in a mouse experimental model [30]. However, in half of the knock-out animals, galectin-3 expression was observed in both cytoplasm and nucleus.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The slides were counterstained using The extent of immunohistochemical staining was estimated by determining a global score, which was calculated by adding the proportion and intensity scores together to produce a total (Σ). 22 haematoxylin (Dako S2020). A haematoxylin-stained histological control slide, which was not exposed to primary antibody, was obtained for each specimen to act as a negative control.…”
Section: Immunochemistry Methodsmentioning
confidence: 99%